Effects of low laser level therapy in rehabilitation of patients with COVID19 pneumonia (Balneo and PRM Research Journal, 2021)
Introduction. An unprecedented public health crisis has been triggered worldwide by SARS-CoV-2’s high contagiosity and it’s mortality rates of 1-5%. Although the majority of COVID-19 cases have a good outcome, there is a small percentage that develop severe pneumonia and citokine storm and may be in the need of mechanical ventilation.Methods. Identifying the exact drivers of the excessive inflammation and the biomarkers that can predict a hyperinflammatory response to SARS-CoV-2 would be extremly helpful in finding efficient anti-inflammatory interventions that may stop the progression to acute respiratory distress syndrome (ARDS).Results. In the search for such interventions we have identified the promising effect of low level LASER therapy (LLLT) on lung inflammation from COVID-19 pneumonia. Due to its well known anti-inflammatory effect and modulatory activity on immune cells, laser therapy may be able to decrease lung and systemic inflammation without affecting lung function in acute lung lesions, relieve respiratory symptoms, normalize respiratory function and stimulate the healing process of lung tissue. The recovery time may also be significantly shortened and all blood, immunological and radiological parameters may improve.Conclusions. This findings need further confirmation from clinical trials but we are hopeful for their contribution on the global battle against COVID-19 pandemic.
Keywords: SARS-CoV-2; pneumonia; low LASER level therapy; anti-inflammatory effect; citokine storm